Assessing Patient Preferences for Shared Decision-Making in Peripheral Artery Disease: Insights From the PORTRAIT Registry. Issue 8 (August 2019) - Provance, Jeremy B.; Spertus, John A.; Decker, Carole; Jones, Philip G.; Smolderen, Kim G.
Abstract : Supplemental Digital Content is available in the text.